Development of Scrapbook for Teaching Descriptive Texts at SMA Sains Plus Tahfidz Qur’an Al Ammar - Mariana; Harianto II; Subagiharti, Heni; Sambayu, Harry; Handayani, Diah Syafitri (International Journal of Educational Research Excellence (IJERE), 2024)
The objective of this research was to develop scrapbook for teaching descriptive text. This research used Model of Development. It was undertaken to develop scrapbook for teaching descriptive text. To gain the purpose, it was needed a research approach that highlights an effort to produce the teaching writing media. Therefore, in designing the model, the researcher used Research and Development approach by adapting Borg and Gall Model. The subject of this research were students of SMA Sains Plus Tahfidz Qur’an Al Ammar at the grade XI in the academic year of 2022/2023. The researcher used two data collection techniques, they were descriptive qualitative data and quantitative data. Qualitative data and quantitative results were obtained from questionnaire validation expert, reviews of material expert and teaching media expert. The data was from the field trials obtained from the comments or responses, questionnaire result and test results. The instruments of data collection were gathered by administrating interview and distributing questionnaire to 22 respondents to get students’ needs. The mean of the questionnaire related to the materials appropriateness is 3.7. The mean value falls into “Good” category since it is in the interval 3.4 < x < 4.2. The result indicates that scrapbbok are appropriate for Grade XI of SMA students. The researcher used test to know the students’ writing skill achievement based on the media used and the test was done twice; pre-test and post-test; pre-test and post-test. Then, t-test was used to analyze the data. The result of the data above is the value of t-test was the value of t-test was higher t table (12,21 > 12,96) at the level significance 0.05 for two tailed and degree of freedom (df) = 22-2 = 20. It means that Scrapbook significantly affects the students’ writing skill achievement.